Experience of targeted Usher exome sequencing as a clinical test. Issue 1 (10th July 2013) - Besnard, Thomas; García‐García, Gema; Baux, David; Vaché, Christel; Faugère, Valérie; Larrieu, Lise; Léonard, Susana; Millan, Jose M.; Malcolm, Sue; Claustres, Mireille; Roux, Anne‐Françoise
Abstract We show that massively parallel targeted sequencing of 19 genes provides a new and reliable strategy for molecular diagnosis of Usher syndrome (USH) and nonsyndromic deafness, particularly appropriate for these disorders characterized by a high clinical and genetic heterogeneity and a complex structure of several of the genes involved. A series of 71 patients including Usher patients previously screened by Sanger sequencing plus newly referred patients was studied. Ninety‐eight percent of the variants previously identified by Sanger sequencing were found by next‐generation sequencing (NGS). NGS proved to be efficient as it offers analysis of all relevant genes which is laborious to reach with Sanger sequencing. Among the 13 newly referred Usher patients, both mutations in the same gene were identified in 77% of cases (10 patients) and one candidate pathogenic variant in two additional patients. This work can be considered as pilot for implementing NGS for genetically heterogeneous diseases in clinical service.